EFFECTIVENESS OF HEALTH EDUCATION ON FAMILY ROLE CHANGES IN POST STROKE PATIENT REHABILITATION AT ARMY HOSPITAL, PEMATANG SIANTAR CITY, 2020 - Doortua, Doortua; Martin, Stephen; Lubis, Josep; Wahyuni Tarigan, Sri; Firdasari, Firdasari (Universitas Efarina, 2021)
Stroke rehabilitation is a program designed to give abilities to sufferers with physical disabilities and/or chronic illnesses, so that they can live or work fully according to their capacity. The rehabilitation program is not only limited to recovering conditions, but also includes rehabilitation that is psychosocial in nature, full of compassion and broad empathy, in order to resurrect sufferers. This research was conducted at the Pematangsiantar City Army Hospital. This study aims to identify the effectiveness of health education on changing the role of the family in the rehabilitation of post-stroke patients. The research design used was a quasy-experimental. According to Arikunto (2006) if the population is less than 100, it is better to take all of them, so that the research is a population study. But if the amount is large, it can be taken between 10%-15% or 20%-25% or more. From the above information, a population of 20% of 105 people is taken with a sample of 21 respondents, and the sampling technique used is purposive sampling, which is based on a consideration made by the researchers themselves, based on previously known characteristics or traits. From the results of the study before health education was carried out, 14% had a bad role, 67% had a good role, and 19% had a very good role. After health education, 62% had a good role, 38% had a very good role. –t count > -t table (-3.914 > -2.086) with p value <0.05 (0.001 <0.05).